2014
DOI: 10.1037/neu0000012
|View full text |Cite
|
Sign up to set email alerts
|

Metacognition in the behavioral variant of frontotemporal dementia and Alzheimer’s disease.

Abstract: Objective Impaired self-awareness is characteristic of nearly all dementias, including Alzheimer’s disease (AD), but the deficit is most severe in the behavioral variant of frontotemporal dementia (bvFTD). The prominence of frontal pathology in bvFTD suggests that failure of online monitoring, the process by which individuals monitor their own cognitive processing in real time, is an important contributor. Metacognitive research offers several approaches to measure self-assessment, some more and others less se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 82 publications
3
64
0
Order By: Relevance
“…Focus on internal visceral signals and constant monitoring and feedback updating of internal predictions are important for the construction of subjective feeling states, and their disruption could explain the patients' behavioural failures [11,70,71]. In this sense, previous reports show that BA10 (i) supports emotional processing of internal states [72], (ii) is related to information retrieval and prospective memory [72] and (iii) could contribute to anosognosia, a typical symptom of dementias [30]. Our results converge with these findings, showing that interoceptive awareness is affected in bvFTD patients, with major compromise of connections between PFC and OFC hubs.…”
Section: (C) Interoceptive Awarenessmentioning
confidence: 98%
See 1 more Smart Citation
“…Focus on internal visceral signals and constant monitoring and feedback updating of internal predictions are important for the construction of subjective feeling states, and their disruption could explain the patients' behavioural failures [11,70,71]. In this sense, previous reports show that BA10 (i) supports emotional processing of internal states [72], (ii) is related to information retrieval and prospective memory [72] and (iii) could contribute to anosognosia, a typical symptom of dementias [30]. Our results converge with these findings, showing that interoceptive awareness is affected in bvFTD patients, with major compromise of connections between PFC and OFC hubs.…”
Section: (C) Interoceptive Awarenessmentioning
confidence: 98%
“…Although this metacognitive dimension has not been examined in neurological populations, impaired awareness and diminished insight are core features of dementia [30,31]. Thus, we predicted that bvFTD and AD would be worse than controls at estimating self-performance.…”
Section: Introductionmentioning
confidence: 94%
“…Different concepts were used to define the construct of awareness [12][13][14][15][16][17][18][19][20] , anosognosia [21][22][23][24][25][26][27][28][29][30][31][32] , self-awareness 33,34 , self -appraisal 35 , insight 36,37 , cognitive insight 38 , metacognition [39][40][41] , unawareness of deficits 42 , awareness of deficit 43,44 , awareness of disease 1,45 , awareness of functioning 46 , awareness of cognitive deficits 47 , awareness of disabilities 48 , awareness of performance 49 , unawareness of memory 42,[50][51][52] , anosognosia of memory 53 , awareness of memory deficits 54,55 , awareness of memory function and functional abilities 56 , unawareness of psychosis or behavioral problems …”
Section: Resultsmentioning
confidence: 99%
“…Metacognition was the knowledge about cognition, including the ability to think about one's own basic cognitive abilities (such as episodic memory or executive functions) 41 . It was also defined as a process by which we understand and alter our own thinking 39 . Some concepts were used to define impairment in awareness, which may range from general to specific impairments, such as anosognosia of memory.…”
Section: Resultsmentioning
confidence: 99%
“…Although previous studies have determined that patients with bvFTD lack empathy, perspective‐taking, insight, and social understanding (Clark et al., 2015; Kumfor & Piguet, 2012; Rosen et al., 2014; Shany‐Ur et al., 2014; Snowden et al., 2008), relatively little is known about how prosociality deteriorates in bvFTD. Recent studies have shown that despite intact perceptions of fairness and basic bargaining skills, patients with bvFTD are unable to use socially relevant contextual information and, therefore, tend to make decisions that benefit themselves over others (Ibanez et al., 2016, 2017; Melloni et al., 2016; O'Callaghan & Hornberger, 2017; O'Callaghan et al., 2016).…”
Section: Introductionmentioning
confidence: 99%